2018
DOI: 10.1002/ep.12972
|View full text |Cite
|
Sign up to set email alerts
|

Influences of magnetic powder addition on the anaerobic digestion of municipal dewatered sludge

Abstract: Magnetic materials were recently developed for sludge disposal because of their advantages. However, the role of magnetic materials in the process of anaerobic digestion of municipal dewatered sludge remains unclear. The aim of this present study is to investigate the magnetic effect factors such as static magnetic field, magnetic nanoparticles, and ordinary magnetic particles on the anaerobic digestion of municipal dewatered sludge. In addition, the biogas production variations and relevant physicochemical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Results have shown that the disintegration performance of waste-activated sludge was effectively improved in the presence of a magnetic field [37]. The magnetic field could improve the AD of municipal sludge to produce biogas [38]. A correlation between the time of exposure to the constant magnetic field and the values of parameters characterizing the methane production was found in the AD of algal biomass [39].…”
Section: Of 21mentioning
confidence: 97%
“…Results have shown that the disintegration performance of waste-activated sludge was effectively improved in the presence of a magnetic field [37]. The magnetic field could improve the AD of municipal sludge to produce biogas [38]. A correlation between the time of exposure to the constant magnetic field and the values of parameters characterizing the methane production was found in the AD of algal biomass [39].…”
Section: Of 21mentioning
confidence: 97%